Business value of enterprise resource planning spending and scope: a post-implementation perspective - Ghobakhloo, Morteza; Azar, Adel; Tang, Sai Hong (Emerald Publishing, 2019)
Purpose – The purpose of this study is to contribute to the existing knowledge about the value of postimplementation Enterprise Resource Planning (ERP) system at the firm level. Design/methodology/approach – A questionnaire-based survey was conducted to collect data from 217 Malaysian firms that successfully implemented ERP system. Data analysis was conducted with partial least squares-structural equation modeling and partial least squares multi-group analysis techniques. Findings – Higher ERP spending and greater ERP scope in the post-implementation stage were associated with higher performance gains. Research limitations/implications – Among other limitations, relying on a small sample size and cross-sectional data of this study and lack of generalizability of findings tend to have certain limitations. An interesting direction for future research would be to extend this study by conducting a multi-level analysis to understand how ERP spending and scope would affect the micro-level performance. Practical implications – Non-financial performance gain is another valuable outcome of ERP implementation. The choice between in-house and off-the-shelf ERP systems will have dramatic impacts on the future profitability of firms. ERP risk management team and related practices during implementation phase result in a significantly higher financial gain in the post-implementation phase. Originality/value – This study assesses the business value of ERP at the post-implementation phase while accounting for key contextual and managerial issues, a topic that has received little attention to date.